Capital's terrorists : Klansmen, lawmen, and employers in the long nineteenth century - Pearson, Chad (The University of North Carolina Press, 2022)
"Through the late nineteenth and early twentieth centuries, employers and powerful individuals deployed a variety of tactics to control ordinary people as they sought to secure power in and out of workplaces. This book suggests that the birth of law and order politics as we know it can be found in nineteenth-century campaigns of organized terror against an assortment of ordinary people across racial lines conducted by Klansmen, lawmen, vigilantes, and union busters"--